Virginia Woolf's influential forebears : Julia Margaret Cameron, Anny Thackeray Ritchie and Julia Prinsep Stephen /: Julia Margaret Cameron, Anny Thackeray Ritchie and Julia Prinsep Stephen. (2015) - Dell, Marion
No abstract available